Agreement among six methods of predicting the anaerobic lactate threshold in elite cross-country skiers - Carter, S. L.; Newhouse, I. (International Journal of Exercise Science, 2019)
The anaerobic lactate threshold (LTan) is used to prescribe training intensity and measure endurance capacity. The LTan identifies a critical point where small increases in workload result in large increases in blood lactate concentration. LTan is usually predicted through visual inspection of a blood lactate (bLa) vs workload plot. Numerous other methods for predicting LTan exist, and the literature lacks a consensus regarding validity of prediction methods. The purpose of this study was to assess the agreement among visual inspection (VI), maximum distance (Dmax) and modified maximum distance (Dmod) from the lactate curve, Baldari & Guidetti (BG), Dickhuth & Heck (DH) and Keul (K) methods for predicting the LTan. Blood lactate data was gathered from 8 male elite cross country skiers across two treadmill running incremental exercise tests. The above methods were used to predict LTan. Bland-Altman limits of agreement and Lin`s Concordance Correlation Coefficient analyses were used to compare methods. Agreement was defined as 95% limits of agreement falling within a maximum allowed difference of ± 0.5 mM bLa between methods. No agreement was found among any of the prediction methods. Mean LTan calculated with the Dmax method was significantly different (p < 0.05) from mean LTan calculated using each other method. We conclude that the six methods for predicting LTan used in this study are not in agreement and should not be considered equivalent for exercise testing purposes. Future studies should compare agreement between LTan methods and the maximal lactate steady state to determine the most valid LTan prediction method.